Ketaklangsungan Ekspresi dalam Lagu Kudangan - Muhamad Hermintoyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2022)
Kudang is a form of sound and song that is issued verbally from the mouth of the father, mother, grandmother, grandfather, brother, uncle, aunt, neighbor, and waitress in the form of an emotional outburst of joy for the baby/small child. Kudangan there are only sounds, not words semantically in the dictionary, they are not found and have no meaning, for example: tak ni nong ninong ninung. While the second form of kudangan is a song/song so that the song “Tak Lelo Lelo Ledhung,” “Timang-timang” appears, whose function is to accelerate the sleep of the baby/child. In the lyrics of the song there is a value of kindness in the form of pitutur/ advice so that it can give parents hope, uphold the good name of parents, have good character so that one day they become useful, living, noble, intelligent and responsible people who can become leaders, both for their families and for their country. Kudang and the lyrics in cuddling are like poetry, which has intrinsic elements that make up poetry, such as diction, rhyme, images and rhetorical means. In this study, the stylistic theory of indirect expression is used. The meaning is using paraphrasing. To get the meaning required language code, literature, and cultural code.